2016
DOI: 10.1016/j.jsps.2015.02.025
|View full text |Cite
|
Sign up to set email alerts
|

A review of polymers as multifunctional excipients in drug dosage form technology

Abstract: In the article, groups of multifunctional polymers used in drug dosage form technology were classified and evaluated. These compounds, in addition to their basic function as excipients, may have additional properties, e.g. stimuli sensitivity, enzyme inhibition, intestinal epithelium penetration enhancement, efflux pump inhibition, taste-masking, pharmacological activity and the ability to interact with enzymes responsible for drug metabolism. While classifying specific groups of multifunctional polymers, spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 66 publications
(101 reference statements)
0
60
0
Order By: Relevance
“…In addition to antimicrobial properties, BC contains immunoglobulins and lactoferrins which help in building up the immunity and protect against pathogenic bacteria proliferation and growth. The mucoadhesive polymers, for example agars, polyacrylates, pectins, sodium carboxymethyl cellulose and xanthan gum, constitute an important group of excipients employed when designing pharmaceutical forms such as tablets, capsules, suspensions and gels (Nallathambi & Gopal, 2014;Karolewicz, 2016). In vitro studies have demonstrated antibacterial activity of EOs against Listeria monocytogenes, Salmonella typhimurium, Escherichia coli O157:H7, Shigella dysenteria, Bacillus cereus and Staphylococcus aureus (Shahbazi, 2015;De Souza, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to antimicrobial properties, BC contains immunoglobulins and lactoferrins which help in building up the immunity and protect against pathogenic bacteria proliferation and growth. The mucoadhesive polymers, for example agars, polyacrylates, pectins, sodium carboxymethyl cellulose and xanthan gum, constitute an important group of excipients employed when designing pharmaceutical forms such as tablets, capsules, suspensions and gels (Nallathambi & Gopal, 2014;Karolewicz, 2016). In vitro studies have demonstrated antibacterial activity of EOs against Listeria monocytogenes, Salmonella typhimurium, Escherichia coli O157:H7, Shigella dysenteria, Bacillus cereus and Staphylococcus aureus (Shahbazi, 2015;De Souza, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It can be incorporated into the lipid bilayers promoting a marking and also mimicking lipophilic drugs since they both exhibit a similar partition coefficient (log P). The confocal laser scanning microscopy study clearly revealed that the dye incorporated into the formulation showed better penetration across the intestinal mucosa as compared to the plain dye solution probably due to the small size of the formulation and presence of PVA which is a nonionic mucoadhesive polymer assuring greater interpenetration [18]. The specific darkening of the intracellular spaces proves the point that the uptake of the dye incorporated into the formulation principally occurred by trans cellular transport.…”
Section: Confocal Laser Scanning Microscopymentioning
confidence: 92%
“…Our data supports that a lower concentration of PVA (1% w/v) is suitable to obtain well-controlled particle size formulations provided stability of dispersion is not compromised. Analysing the response surface of interactions of PLGA and ethyl acetate at constant PVA, we found that initially, with an increase of solvent volume, the particle size did not change much and then decreased with further increase in the volume of ethyl acetate (trial [13][14][15][16][17][18][19][20].…”
Section: Influence On Particle Sizementioning
confidence: 99%
“…Forexample, nanoparticles with a hydrodynamic diameter of 5-100 nm have optimal pharmacokinetic properties for in vivo applications. [7][8][9][10] These polymeric nanoparticles are prepared from a variety of biocompatible polymers and can be formulated to transport pharmaceutical agents in a controlled and targeted fashion through further surface modification drugs and modulate dendrimer-drug interactions. 6 Now a days, polymeric nanoparticles have been extensively studied for their chemical and physical properties and widely used in drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%